Law Enforcement in the Financial Sector in Indonesia and United Kingdom: A Sadd al-Dharai’ Approach to Regulation and Oversight - Kholil, Suparman; Sunaryo, Oyo; Khosiah, Siah; Ahmad, Yusuf (DIKTUM: Jurnal Syariah dan Hukum, 2025)
The financial sector is crucial to economic stability but remains vulnerable to violations such as digital fraud and money laundering. These challenges require robust law enforcement mechanisms grounded in both traditional and modern governance principles. This study aimed to analyze regulatory frameworks, supervisory mechanisms, and preventive governance in Indonesia’s financial sector using Sadd al-Dharai’. A qualitative approach with normative juridical methods was employed, focusing on secondary data analysis. The research identified regulatory comprehensiveness, institutional effectiveness, and preventive governance as key dimensions. While Indonesia’s legal frameworks are strong, gaps in addressing technological and global challenges remain. Sadd al-Dharai’ emphasizes proactive measures to mitigate financial risks. Practically, the study recommends updating regulations, enhancing institutional collaboration, and integrating advanced technologies. Theoretically, it highlights the relevance of Islamic principles like Sadd al-Dharai’ in addressing contemporary financial challenges, providing a foundation for future research in preventive governance.